Scan and rob! Convenience shopping, crime opportunity and corporate social responsibility in a mobile world. Issue 4 (October 2017) - Beck, Adrian; Hopkins, Matt
Abstract One of the unintended consequences of technological innovation is that it can promote opportunities for crime. These opportunities not only have the potential to generate significant financial costs but can also have wider social consequences. This article considers the development of technologies designed to enable customer convenience in the retail sector, and focuses specifically on the potential of mobile scan and payment systems to generate opportunities for crime. Through interviews with retailers, store observations and analysis of shrinkage data both the potential opportunities for crime and impact on loss are identified. The wider potential criminogenic impact of such innovation is also considered and whether large businesses have a social and moral responsibility to mitigate for any negative effects of such developments.